2015
DOI: 10.1161/strokeaha.114.008648
|View full text |Cite
|
Sign up to set email alerts
|

Occult Anterograde Flow Is an Under-Recognized but Crucial Predictor of Early Recanalization With Intravenous Tissue-Type Plasminogen Activator

Abstract: Background and Purpose-Thrombolysis depends on the ability of blood and thrombolytic agents to permeate thrombus.We devised a novel technique to quantify blood permeating through thrombi and determine whether this parameter predicts early recanalization with intravenous tissue-type plasminogen activator. Methods-Intravenous tissue-type plasminogen activator-treated patients with stroke and complete occlusion on computed tomographic angiography were analyzed using perfusion computed tomography and a delay insen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Our findings on the increased rate of intravenous r-tPAinduced recanalization with increasing perviousness is consistent with both preclinical 6 and clinical studies. [13][14][15] In a previous study using lysis modeling of fibrin thrombi with various permeability, it was demonstrated that lysis would require hundreds of minutes in impermeable thrombi. 6 Other studies demonstrated an association between success of recanalization after intravenous r-tPA and qualitative assessment of flow passing through a thrombus for both ischemic stroke and coronary occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings on the increased rate of intravenous r-tPAinduced recanalization with increasing perviousness is consistent with both preclinical 6 and clinical studies. [13][14][15] In a previous study using lysis modeling of fibrin thrombi with various permeability, it was demonstrated that lysis would require hundreds of minutes in impermeable thrombi. 6 Other studies demonstrated an association between success of recanalization after intravenous r-tPA and qualitative assessment of flow passing through a thrombus for both ischemic stroke and coronary occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…6 Other studies demonstrated an association between success of recanalization after intravenous r-tPA and qualitative assessment of flow passing through a thrombus for both ischemic stroke and coronary occlusion. [13][14][15] Because perviousness increased the odds of recanalization, and recanalization is associated with improved functional outcome, it is not surprising that there is a direct relation between perviousness and favorable functional outcome in the intravenous r-tPA group. However, this association was still significant after adjusting for recanalization in a multivariate model.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, further work should explore the effects of other thrombus attributes such as thrombus density and contrast permeability on treatment outcomes. 4,[13][14][15] Advances in biomechanical characterization of thrombi will aid in optimizing endovascular devices and techniques. Until more data are available, TL measurement should not be used for treatment decision making.…”
Section: Strokementioning
confidence: 99%
“…In addition, anterograde flow across occlusion sites of cerebral arteries could be distinguished from retrograde collateral filling noninvasively by 4-D CTA [44]. In addition to this indirect contribution of CTP to imaging of occluded vessels, a recent study shows a direct parameter of CTP that can be used to evaluate the occult anterograde flow of cerebral artery occlusion in acute stroke patients [45]. Using perfusion maps that measure delay in arrival time of contrast within the intracranial artery tree (T0 maps), a positive sloped regression line of T0 values measured along artery silhouette distal to clot was observed as a marker of occult anterograde flow (permeable clot).…”
Section: Computed Tomography Perfusionmentioning
confidence: 99%